Fabrication of right triangular prism retroreflectors through 3½½-axis ultraprecise single point inverted cutting. Issue 5 (29th July 2017) - Hamilton, Benjamin W.; Hussein, Sama; Milliken, Nicolas; Tutunea-Fatan, O. Remus; Bordatchev, Evgueni V.
ABSTRACT: Retroreflectors (RR) are passive optical structures that are capable of returning incident light back to the source. The focus of the current study is represented by the right triangular prism (RTP) geometry which could be a more efficient alternative to the traditional inverted corner cube geometry. While current manufacturing practices rely solely on the use of conventional pin-bundling techniques, the work reported in this study presents further enhancements of the previously introduced ultraprecise single point inverted cutting technique which can be used in a manner approximately similar to 3½½-axis kinematics. The experimental results obtained have demonstrated both the feasibility of the proposed fabrication approach as well as the optical viability of the fabricated RTP elements. GRAPHICAL ABSTRACT: